Alcohol and economic development: Observations on the kingdom of Bhutan. (24th February 2016) - Kypri, Kypros; Dorji, Gampo; Dalton, Craig
Abstract: Bhutan is a small country undergoing rapid social change arising from income growth, urbanisation and Western cultural influence. Markers of poverty, namely infectious disease and infant mortality, have improved dramatically. The attention of health authorities is now focused on the non‐communicable disease and injury burdens, to which alcohol consumption is a major contributor. The paper draws on official data to characterise the consumption of alcohol and related harm, and the nature of the alcohol market, with commentary on crucial aspects of availability policies and drink‐driving regulation that need reform. Kypri K, Dorji G, Dalton C. Alcohol and economic development: Observations on the kingdom of Bhutan. Drug Alcohol Rev 2017;36:333ȃ336.]